Notices (Blackfriars, 1959)
The English Eccentrics, by Edith Sitwell In The Firsyborn, by Chrisopher Fry Happiness With God, by Dom Basil Whelan, O.S.B. Sainte Madeleine SilentBedes, by S. G. A. Luff One Nun to Another, by Sister Marry Laurence, O.P.